Measurement of the time-dependent CP asymmetries in B0s → J/ψK0S - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; et al. (Journal of high energy physics, 2015)
The first measurement of decay-time-dependent CP asymmetries in the decay B0s → J/ψK0S and an updated measurement of the ratio of branching fractions B(B0s → J/ψK0S)/B(B0 → J/ψK0S) are presented. The results are obtained using data corresponding to an integrated luminosity of 3.0 fb−1 of proton-proton collisions recorded with the LHCb detector at centre-of-mass energies of 7 and 8 TeV. The results on the CP asymmetries are A∆Γ(B0s → J/ψK0S) = 0.49 ±0.650.77stat±0.06syst, Cdir(B0s → J/ψK0S) = −0.28 ± 0.41(stat) ± 0.08(syst), Smix(B0s → J/ψK0S) = −0.08 ± 0.40(stat) ± 0.08(syst). The ratio B(B0s → J/ψK0S)/B(B0 → J/ψK0S) is measured to be 0.0431 ± 0.0017(stat) ± 0.0012(syst) ± 0.0025(fs/fd), where the last uncertainty is due to the knowledge of the B0s and B0 production fractions.
Im Titel sind "0" und "s" untereinander geschrieben: "0" hochgestellt, "s" tiefgestellt
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, C. Voß, S. Wandernoth, D. Wiedner, A. Zhelezov [und 665 weitere]
Gesehen am 08.10.2020